2015
DOI: 10.1155/2015/173165
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Migraine as a Chief Complaint in Otolaryngology Outpatient Practice

Abstract: Objective. To identify the frequency of typical (headache and dizziness) and common atypical (ear fullness, pressure, pain, tinnitus, facial fullness, and nasal congestion) migraine symptoms as chief complaints among patients presenting to otolaryngology clinic. Methods. This is a descriptive study of prospectively collected data from a general otolaryngology practice. Typical migraine presentations were diagnosed by applying international headache society (IHS) criteria for migraine headache and Neuhauser's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The prevalence of VM in previous studies was dependent on different diagnostic criteria and study populations. Prior to the current diagnostic criteria, the prevalence of VM was 9%-11.9% in headache clinics, 4.7%-29.3% in otolaryngology clinics, and 6%-25.1% in specialized dizziness clinics (4,11,14,19,20,23). Only one study assessed the prevalence of VM based on the consensus criteria formulated by the Barany Society and the IHS; 4.2% were assigned to the definite VM group and 5.7% to the probable VM group in a tertiary referral otolaryngology clinic (12).…”
Section: The Prevalence Of Vmmentioning
confidence: 99%
“…The prevalence of VM in previous studies was dependent on different diagnostic criteria and study populations. Prior to the current diagnostic criteria, the prevalence of VM was 9%-11.9% in headache clinics, 4.7%-29.3% in otolaryngology clinics, and 6%-25.1% in specialized dizziness clinics (4,11,14,19,20,23). Only one study assessed the prevalence of VM based on the consensus criteria formulated by the Barany Society and the IHS; 4.2% were assigned to the definite VM group and 5.7% to the probable VM group in a tertiary referral otolaryngology clinic (12).…”
Section: The Prevalence Of Vmmentioning
confidence: 99%
“…Approximately 10.8% of patients had a migrainous chief complaint in otolaryngology outpatient practice [16]. Almost 90% of sinus headache patients were determined to have migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Vertigo can arise in the context of a headache attack (preceding, occurring with, or after) [17] or between attacks, and the temporal relationship is extremely varied [3]. Vertigo episodes have a variable duration from clusters of seconds (10%), occurring repeatedly for a period of time, to attacks during minutes (3%) [38], days (30%), and rarely weeks [2, 39]. By definition, they last from minutes to hours or days (usually, less than 72 h), with the sum of the clusters being considered as one attack.…”
Section: Migraine Clinical Manifestationsmentioning
confidence: 99%
“…Studies in tertiary headache clinics reveal great variability in prevalence in different series and according to the clinical context: 4.7–29.3% in an otolaryngology clinic and 9–11.9% in a headache clinic [7, 17, 26, 38]. A recently retrospective, observational, and descriptive study [40] performed in an outpatient clinic revealed that VM affects more middle-aged women than men and that migraine was diagnosed before vertigo in the majority of the situations [40].…”
Section: Migraine Clinical Manifestationsmentioning
confidence: 99%